PENGARUH INDEKS PEMBANGUNAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (IP-TIK), TINGKAT PENGGUNA INTERNET, DAN UANG ELEKTRONIK TERHADAP PERTUMBUHAN EKONOMI PADA 34 PROVINSI DI INDONESIA - Nurlia Aprianti Sinurat; Putri Sari Margaret Julianty Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In recent years, Indonesia’s economic growth has continued to increase, however disparities in growth among provinces remain, reflecting the uneven distribution of economic development. On the other hand, the development of information and communication technology, internet usage, and electronic money varies across provinces and therefore has the potential to influence economic growth. This study aims to analyze the effect of the information and communication technology development index (ICT-DI), internet user rate, and electronic money on economic growth in Indonesia. This research employs a quantitative approach using panel data, which combines time series data from 2020-2024 and cross-sectional data from 34 provinces in Indonesia. The analysis was conducted using panel data regression, with the Fixed Effect Model (FEM) identified as the most appropriate model. The results indicate that, partially, the ICT Development Index has a positive and significant effect on economic growth, with a probability value of 0.0087. The internet user rate has a negative and insignificant effect, with a probability value of 0.9508. Meanwhile, electronic money has a positive and significant effect on economic growth, with a probability value of 0.0045. Simultaneously, the three variables have a significant effect on economic growth, as indicated by the F-statistic probability value of 0.000000. The Adjusted R-squared value of 0.527645 shows that 52.76 percent of the variation in economic growth can be explained by the variables included in this study.